From Waḥdat al-Wujūd to Waḥdat al-Adyān: Reconstructing Ibn ʿArabī’s Conceptualisation of Religious Diversity - Sobar Al Ghazal; Muhtar Solihin; Munir Munir; Radea Yuli A. Hambali (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
This article seeks to reconstruct the concept of Waḥdat al-Adyān (the Unity of Religions) within the thought of Ibn ʿArabī and to assess its relevance through a comparative analysis with the Perennial Philosophy. The significance of this study lies in addressing the often reductive interpretations of the unity of religions, which have tended either towards an unqualified form of religious pluralism or as a rationale for theological exclusivism, thereby necessitating a more nuanced conceptual reconstruction. Employing a qualitative methodology, this research undertakes philosophical and conceptual analyses of Ibn ʿArabī’s principal works alongside those of prominent perennialist thinkers, notably Frithjof Schuon and Seyyed Hossein Nasr. The findings reveal that, from Ibn ʿArabī’s perspective, religious diversity is an ontological consequence of the manifestations of the Infinite Absolute Reality (al-Ḥaqq), rather than a contradiction of truth. The reconstruction of Waḥdat al-Adyān is articulated through three interrelated dimensions: ontological, epistemological, and theological. Ontologically, religious diversity is construed as the phenomenal expression of a single ultimate reality; epistemologically, plurality is attributed to the limitations inherent in human understanding; and theologically, the concept recognises a hierarchy of truth while affirming the possibility of salvation for sincere seekers of truth. This study contributes to the advancement of Islamic intellectual scholarship by proposing a metaphysical model that reconciles the unity of ultimate reality with religious diversity, thereby offering a philosophical foundation for interreligious dialogue that eschews both exclusivism and relativism.